본문 바로가기
기초부터 대학원 수학까지, 추상대수학

28. 추상대수학 (h) 직접곱, 직접합

by EnjoyingMath 2023. 9. 7.
반응형

다음 포스팅은 https://youtu.be/mbl_xp6JxPA 의 영상에서 작성한 노트의 핵심을 정리한 것입니다. 여러 오탈자 및 수정 사항들이 있을 수 있습니다. 노트 내용에 대한 디테일한 설명들은 영상을 참고하시길 바랍니다.

 

Direct-product, direct-sum.

Proposition. Given a gp G,

(1) $\phi \neq H, K \leq G$.

Then $H K=\{h k \mid h \in H, k \in K\} \leq G$

if and only if $H K=K H$.

(2) If $H \unlhd G$ and $k \leq G$, then $H K=k H$.

(3) If $H \unlhd G$ and $K \unlhd G$, then $H K \unlhd G$.

(4) If $H \unlhd G$ and $K \unlhd G$ and $H \cap K=$ {e}

then $\underbrace{H K}_{\text {Internal direct produce }} \cong \underbrace{H \times K}_{\text {extenal direct product }}=\left\{\left(h_{1} k\right) \mid h \in H_{1}, k \in k\right\}$ 

Proof. (1) $\Leftrightarrow$ ) Let $H K \leq G$.

We will show $HK\subseteq KH$ and $KH \subseteq HK$

$C$ : take any $hk\in HK$

claim: $kh\in KH$

Since $HK \leq G, h k \in H K \Rightarrow(h k)^{-1} \in H K$.

Then $k^{-1} h^{-1}=h_{0} k_{0}$ for some  $h_0 \in H, k_{0} \in K$

$
\begin{aligned}
\Leftrightarrow & \left(K^{-1} h^{-1}\right)^{-1}=\left(h_{0} k_{0}\right)^{-1} \\

& h K=K_{0}^{-1} h_{0}^{-1} \in K H .
\end{aligned}
$

Similarly, $K H \subseteq H K$. Thus $K H=H K$.

$\Leftrightarrow$ Suppose $H K=K H$.

Claim: HK $\leq G$.

Note that $e=e \cdot e \in H K \neq \varnothing$.

Claim: Let $h_{0} k_{0}, h_{1} k_{1} \in H K$.

$
\begin{gathered}
\text { Then } h_{0} k_{0}\left(h_{1} k_{1}\right)^{-1} \in H K \text {. C Subgp  } \\
h_{0} k_{0} k_{1}^{-1} h_{1}^{-1}
\end{gathered}
$

Since $H K=K H, K_{0} K_{1}{ }^{-1} h_{1}^{-1}=h_{2} K_{2}$ for some $h_{2} \in H_{1} K_{2} \in K$.

$
\Rightarrow h_{0} K_{0} K_{1}^{-1} h_{1}^{-1}=h_{0} h_{2} K_{2} \in H K \quad \cdots \text { (1). }
$

(2) Let $H \unlhd G$ and $K \leq G$.

claim: $H K=K H (=) \subseteq$ and $⊇(V)$ 

Take any $h_0 k_0 \in HK$

We will show $h_0k_0 \in K H$.

Note that $h_{0} K_{0}=K_{0} k_{0}^{-1} h_{0} k_{0} \in K H$.

Also, for any $k_{1} h_{1} \in K H$,

$k_{1} h_{1}=k_{1} h_{1} k_{1}-1 k_{1} \in H k_{2} \cdots \text { (2) }$


(3) Let $H \unlhd G$ and $K \unlhd G$. Then $H K \leq G$ by 2 and 1

claim: $HK\unlhd G$

Take any $h_0 k_0 \in HK$ and $g \in G$.

NTS: $g h_{0} k_{0} g^{-1}$ $\in HK$

Note that $g h_{0} k_0 g^{-1}=g h_{0} g^{-1} g k_{0} g^{-1} \in H K $  (V) $\cdots (3)$ 



(4) Let $H \unlhd G$ and $K \unlhd G$ and $H \cap K=$ {e}

By (3), $H K \unlhd G$.

NTS: $HK=H \times K$ as gps


define $f: H \times K \longrightarrow H K$
                   $(h, k) \longmapsto h k \text {. }$

Then $f$ is well -defined.

 If $\left(h_{1} k_{1}\right)=\left(h_{2}, k_{2}\right)$ then $h_{1} k_{1}=h_{2} k_{2}$.
       $\Leftrightarrow h_{1}=h_{2}, k_{1}=k_{2}$


claim: $f$ is gp homo.

Take any $\left(h_{0} , k_{0}\right),\left(h_{1} k_{1}\right) \in H \times K$.

$
\begin{aligned}
& \left.f\left(\left(h_{0}, k_{0}\right) \cdot C h_{1} k_{1}\right)\right) \stackrel{?}{=} f\left(h_{0}, k_{0}\right) f\left(h_{1} k_{1}\right) \\
& f\left(h_{0} h_{1}, k_{0} k_{1}\right)=h_{0} h_{1} \mid k_{0} k_{1}^{\prime \prime} ?
\end{aligned}
$

Note that

$
\begin{aligned}
h_{0}, k_{0} k_{1} \stackrel{?}{=} h_{0} k_{0} h_{1} k_{1} & \Leftrightarrow h_{1} k_{0} \stackrel{?}{=} k_{0} h_{} \\
& \Leftrightarrow h_{1} k_{0} h^{-1} \stackrel{?}{=}{\stackrel{}{K_{0}} } \\
& \Leftrightarrow h_{1} k_{0} h_{1}^{-1} k_{0}^{-1} \stackrel{?}{=} e
\end{aligned}
$

Since $K \unlhd G,\left({h}_{1} k_{0} h_{1}^{-1}\right) k_{0}^{-1} \in K$.

on the other hand, $H \unlhd G \Rightarrow h_{1}\left(k_{0} h_{1}^{-1} k_{0}^{-1}\right) \in H$.

$
\Rightarrow h_{1} K_{0} h_{1}^{-1} K_{0}^{-1} \in K \cap H=\text \{ e \}$


claim: $f$ is injective

Let $f\left(h_{1} k_{1}\right)=f\left(h_{2}, k_{2}\right)$

$\Leftrightarrow k_{1} k_{2}^{-1}=h_{1}^{-1} h_{2} \in K \cap H=\{e\}\ (=) k_{1}=k_{2}, h_{1}=h_{2}$.

claim: $f$ is onto.

Tale any $hk \in HK, $ $f(h, k)=h k$.

Def Given an index set I, 

$\forall i \in I, \quad$ $Gi$ is a gp. 

define $\Pi G_{i}:=\left\{f: I \longrightarrow \bigcup G_{i} | f(i)\in G_i,\forall i\in I\right\}$

: direct product of $\left\{G_{i}\right\}_{i} \in I$



Remark.

$A \times B=\{(a, b) \mid a \in A, b \in B\}$.

$=\left\{f:\{1,2\} \rightarrow A \cup B \mid \begin{array}{l}
f(1) \in A \\
f(2) \in B
\end{array}\right\}$

$\begin{aligned}
& A_{1} \times A_{2} \times \cdots \times A_{n}=\left\{\left(a_{1}, \cdots, a_{n}\right)\left|a_{i} \in A_{i}\right| 1 \leq{i} \leq n\right\} \\
& \left.=\{f:{1,}\cdots, n\right\} \rightarrow \bigcup_{i=1}^{n} A_{i}\left|f(i) \in A_{i }\right|1 \leq{i} \leq n\}
\end{aligned}$

Remark.

In a Vector notation,

$\Pi_{i \in I} G_{i}=\left\{\left(a_{i}\right){i} \in I\right\} \text {. }$

We give the binary operation on $\Pi G_i$ :

given $f_{1} g \in \prod_{i \in I} G_{i}, f * g: I \longrightarrow \bigcup_{i \in I} G_{i}$

$(f * g)(i)=f(i) *_{i} g(i)$

i.e., $\Pi_{i \in i} G_{i}$ is a $gp$

Def Given an index set I, $G_i: gp$ for each $i\in $ $I$

define $\bigoplus_{i \in I} G_{i}:={f:I \longrightarrow \bigcup G_i : f_{(i)}\in G_i \forall i }$

all but finitely many $i$'s


In particular, $\bigoplus_{i \in I} G_{i} \leq {\Pi}_{i \in I} G_{i}$

Called the direct Sum of $\{G_{i}\}_i \in$ $I$

element: $\left(a_{1} a_{2}, \cdots, a_{n,}, e, \ldots, e_{1} . ..\right)$

RMK If $|I| < \infty$, $\bigoplus Gi=\pi Gi$

반응형